A Review on Back-to-Back Converters in Permanent Magnet Synchronous Generator based Wind Energy Conversion System - Karthikrajan Senthilnathan; K. Iyswarya Annapoorani (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This paper presents a review on the application of back-to-back converters in the field of Permanent Magnet Synchronous Generator (PMSG) based Wind Energy Conversion Systems (WECS). The wide applications of the back-to-back converters are power conditioning devices, micro grid, High Voltage Direct Current (HVDC), Renewable energy systems. The intention is to present an overview about the design considerations taken by various researchers in back-to-back converters in the field of Wind Energy Conversion Systems (WECS) and recent developments on it. Generally the configuration of back-to-back converters used are 12 pulse Voltage Source Converters (VSC), 12 pulse Current Source Converter (CSC), 9 Pulse Voltage Source Converter.